If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2y + 4z = 0 Solving 3x + 2y + 4z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 3x + 2y + -2y + 4z = 0 + -2y Combine like terms: 2y + -2y = 0 3x + 0 + 4z = 0 + -2y 3x + 4z = 0 + -2y Remove the zero: 3x + 4z = -2y Add '-4z' to each side of the equation. 3x + 4z + -4z = -2y + -4z Combine like terms: 4z + -4z = 0 3x + 0 = -2y + -4z 3x = -2y + -4z Divide each side by '3'. x = -0.6666666667y + -1.333333333z Simplifying x = -0.6666666667y + -1.333333333z
| 3x+6xy=153 | | 1/2x-9=3/4x-5 | | 7r=9t+3 | | 7x-7y-5x+9y= | | 116-75=x | | (5x+2)-(3x+4)=0 | | 8y-3+8y-3=2y | | 10.08+9y=6 | | -3x-12=o | | 22.5-2y=-5 | | (ln)(y)=.61 | | -7x-2/8=-9 | | (6x-9)-(3x+8)=4(x-11) | | -15x^2+27= | | (y-8)(y-3)= | | 3x+6x+9= | | 8x+4x+12= | | 15x+3y=-6 | | 6(x+5)=3[2(2x-3)+1]+5 | | 5(3x-4)=2-2x | | C=0.75n+140 | | 42y+28x= | | 9x+y=10solvey | | -4v+35=-8v+7(5-2v) | | 3(u-5)-7u= | | 5a+b+0.1c=100 | | 17*17=8*8+x*x | | -23x+13y=-29 | | 1/2(44)-3/5=3/5(44)-5 | | 9p+n=84 | | 4x^2y=5 | | 0.05(y-300)=105-0.1y |